Organizational Justice and Employee Deviance among Emergency Services Personnel in Malaysia - Lee, Leong Weng; Abdullah, Muhammad Madi bin (Journal of Contemporary Research in Business, Economics and Finance, 2019)
Fairness in the workplace is imperative in the emergency services sector. Most of the organizational justice and workplace deviance literature addresses the non-emergency services perspective, while research involving the emergency services personnel have been lacking. The aim of the present study is to examine the relationship between emergency services personnel perception of organizational justice and employee deviance. A cross-sectional field survey was conducted utilizing a sample of 209 in 10 Emergency Services Centers in Malaysia. Employees rated fairness in the distribution of outcomes and rewards (distributive justice), fairness in interaction with managers (interpersonal justice) and candid explanation (informational justice), fairness in procedures implementation (procedural justice) and the frequency to exhibit deviant behaviors at work (employee deviance). Analysis results revealed that low levels of interpersonal justice and informational justice predicted deviant acts targeted at other individuals, while low levels of distributive justice and informational justice predicted deviant acts targeted at the organization. This study adds to the growing body of research on employee deviance literature by empirically validating the workplace deviance typology in an emergency services setting and by examining four types of organizational justice simultaneously on employee deviance.